Evaluación de la producción de energía eléctrica y disminución de DQO en agua residual sintética mediante celdas de combustible microbianas a escala laboratorio (2017)
In the present research project covers the evaluation of the production of electrical energy and decline of cod in a synthetic residual water, through the action of two bacteria, Escherichia coli and Pseudomonas aeruginosa under optimal conditions of growth and special operating conditions in the cell, as electrodes were used graphite and carbon fabric. Escherichia coli was the bacteria that with certain conditions of pH, temperature, mediator and the electrode material was obtained the highest values of voltage, measured in mV, which combinations described in the design of experiments, in addition, it was possible to obtain a significant reduction with the bacteria in the chemical oxygen demand.